RESEARCH ON BIOMASS BRIQUETTE AS AN ALTERNATIVE ENERGY FROM PTEROCARPUS INDICUS LEAVES AND TWIGS WASTE - Jovian Evander; Willyanto Anggono; Teng Sutrisno (Mechanova, 2016)
Indonesia has a variety of plant species which are very useful for life. Plants that have a lot ofbenefits that include Pterocarpus indicus. This plant is commonly used as greening because of thecharacteristics that have dense leaves and rapid growth. During the rainy season, the leaves andtwigs of this plant will often fall fallen because with the wind and rain. In the summer, the leaveswill fall due to dry. The actual leaves and twigs can be used as an alternative fuel in a way that isgood and correct processing. Alternative fuels is that biomass briquettes. This research wasconducted with the aim of knowing the potential of the plant Pterocarpus indicus for biomassbriquettes made with raw materials leaves and twigs Pterocarpus indicus and tapioca starchadhesive material. This research will be tested to determine whether the calorific value of the leavesand twigs Pterocarpus indicus can be used as biomass briquettes. The composition ratio of rawmaterials and adhesives as follows: 100%, 90%, 80%, 70%, 60%, 50%. Tests using a bombcalorimeter calorific value. From the experimental results show that the best composition is 90%raw materials and 10% adhesives